Multiple performance characteristics optimisation in side and face milling of glass fibre reinforced polyester composite at different weightage of performances by grey relational analysis. (2017) - Roushan, Ashutosh; Bandyopadhyay, Asish; Banerjee, Simul
The delamination is a severe problem related with the milling of e-glass fibre reinforced polyester composites. Glass fibre reinforced polyester is a composite which gives best strength to weight ratio. It has huge requirement in aerospace industry, naval industry, automobile industry, chemical industry, wind power station and marine industry due to properties like high strength, light weight, low thermal expansion, good dampness, good electrical insulation, non-magnetic and corrosion resistance. During the milling operation, the process parameters like rotational speed, feed rate, depth of cut and cutter speed etc. greatly affect the delamination and surface quality. In the present investigation, therefore, feed rate, rotational speed, depth of cut and cutter diameter are chosen as milling parameters. Delamination factor, average surface roughness and material removal rate are taken as responses. Experiments have been conducted based on Taguchi's L9 (3 4 ) orthogonal array design. Analysis has been done based on grey-relational analysis.